Злочин і покарання як філософсько-правова проблема - Крисюк, Ю.; Krysiuk, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглядається історіософська ретроспектива обґрунтування понять «злочин» і «покарання» в різних філософсько-правових теоріях, їх взаємозв’язок та вплив на реформування сучасного кримінального й кримінально-виконавчого права в Україні, а також проблема адекватності покарання правопорушенню. The article is about the historiosophical retrospection of argumentation of the concepts of «crime» and «punishment» in various philosophical and legal theories, their interrelation and influence on the reforming of the modern penal and criminal and executive law in Ukraine, and also about the problem of adequacy of punishment for an offence. In particular three approaches to the essence of punishment have been pointed out in the article. The first one deals with the theories which consider the right to punish as the right of society for self-defence. The second one concerns the concept of punishment as the embodiment of justice. The supporters of this theory justify punishment application on the grounds of the necessity to establish moral order in society. Supporters of the third approach consider legal order to be a necessary element of public life, and it needs to be protected from encroachments. The state as the form of public association of people establishes standards of behavior, and ensures law and order which regulate coexistence of individuals. Rules of law are the expression of their interests. Punishment appears as protection of these interests and generally-accepted way of life.
Crime and Punishment as Philosophical and Legal Problem
Keywords: злочин; покарання; справедливість покарання; невідворотність покарання; філософсько-правові теорії; кримінальне право України; кримінально-виконавче право України; crime; punishment; justice of punishment; inevitability of punishment; philosophical and legal theories; criminal law of Ukraine; penal law of Ukraine